Estudio sobre la realización de algunas consonantes en coda en el habla popular de la Ciudad de México: hacia una interpretación causal de los hechos - Arias Álvarez, Beatriz (Boletín de Filología, 2007)
It has been stated that Mexico City Spanish, due to its marked consonantism, tends to keep the so called educated consonant clusters; nevertheless, in popular speech in this city one can find realizations of tbe consonant in implosive position that do not conform to that statement. The phenomena registered and analysed in this research, many of them disregarded in other studies, can be put together in tlhe following groups: a) weakening or lenition processes (voicing, fricativization, vocalization and loss), based on the Spanich preference for the CV pattern; b) acoustic equivalence processes; and c) assimilation processes. Besides, in this analysis we vesi@ that many of rnechanisms studied are also registered in the history of Castilian and shared with ober romance languages.